Objects of desire the modern still life. - Rowell, M. (New York : Harry N. Abrams, 1997)
Arman ; Babij, Iwan ; Baselitz, Georg ; Beckmann, Max ; Boccioni, Umberto ; Braque, Georges ; Broodthaers, Marcel ; Bruce, Patrick Henry ; Carrà, Carlo ; Christo ; Cornell, Joseph ; Cragg, Tony (Anthony) ; Cézanne, Paul ; Dali, Salvador ; Davis, Stuart ; De Chirico, Giorgio ; Derain, André ; Dine, Jim ; Dubuffet, Jean ; Duchamp, Marcel ; Dufy, Raoul ; Ensor, James ; Fontana, Lucio ; Gnoli, Domenico ; Gober, Robert ; Gris, Juan ; Guston, Philip ; Hamilton, Richard ; Höch, Hannah ; Jawlensky, Alexej von ; Johns, Jasper ; Kahlo, Frida ; Klee, Paul ; Koons, Jeff ; Laib, Wolfgang ; Larionov, Mikhail ; Laurens, Henri ; Le Corbusier ; Leger, Fernand ; Lichtenstein, Roy ; Magnelli, Alberto ; Magritte, René ; Man Ray ; Manzoni, Piero ; Matisse, Henri ; McCollum, Allan ; Merz, Mario ; Miro, Joan ; Mondriaan, Piet ; Morandi, Giorgio ; Morris, Robert ; Murphy, Gérald ; Oldenburg, Claes ; Oppenheim, Meret ; Ozenfant, Amédée ; Picabia, Francis ; Picasso, Pablo ; Puni, Iwan ; Rauschenberg, Robert ; Ray, Charles ; Redon, Odilon ; Richter, Gerhard ; Riverhead (New York) ; Ruscha, Ed ; Schamberg, Morton ; Sherman, Cindy ; Smith, Kiki ; Soutine, Chaim ; Spoerri, Daniel ; Therrien, Robert ; Warhol, Andy
boek